The fox and the crow - Robbins; Rita (Jamaica Mind to Mind, 2016)
The tale highlights the themes of flattery and cunning, teaching children about the dangers of being deceived by compliments and the importance of being cautious. The book uses simple text and engaging illustrations to make the lesson accessible and entertaining for preschoolers.